Lasting and extensive consequences of left mesial temporal lobe seizures on electrical cortical activity - Mathieu Dhoisne; Nacim Betrouni; Sophie Hennion; Lucie Plomhause; Arnaud Delval; Philippe Derambure (NeuroImage)
Background and objectives: Focal epilepsies disrupt long-range networks with seizure recurrence driving both regional and global alterations in connectivity networks. While prior studies have focused on the interictal consequences, limited data exist on the direct aftermath of focal seizures. We hypothesize that mesial temporal lobe seizures lead to enduring cortical disorganization. The aim was to assess the effects of a mesial temporal lobe seizure on cortical activity and understand how the side of seizure onset influences these consequences. Methods: In this retrospective study, high-resolution EEG of patients with mesial temporal lobe epilepsy (mTLE) were analyzed. Groups of patients were identified based on the side of seizure onset. We compared relative powers in different frequency bands between interictal (prior to the seizure) and late postictal (one hour following the seizure) periods. Network-based statistics were employed to compare functional connectivity at source level between periods. Results: Twenty-three patients were included (13 left and 10 right mesial temporal lobe seizures). In patients with left mTLE, we observed a post-seizure increase in the relative spectral power in the delta band (p = 0.001) and a decrease in the relative spectral power in the alpha band (p = 0.013) over the left temporofrontal regions. We isolated a subnetwork that presented a decrease in connectivity strength in alpha band, primarily involving long-range left hemisphere connections (p = 0.042). We also identified a subnetwork that presented a decrease in connectivity strength in theta band, primarily involving interhemispheric connections (p = 0.039). No significant post-seizure changes were found in patients with right mTLE. Discussion: Left mesial temporal lobe seizures appear to be associated with lasting and widespread disorganization of cortical activity. We propose that the postictal state is associated with a prolonged functional deafferentation of the affected region in patients with left mTLE. This leads to a widespread disorganization of the functional networks, which may be associated with cognitive impairments and promote the progression of epilepsy. Further studies are required to fully understand the functional repercussions.